Simulating the context of interpreter-mediated social work interactions via interprofessional education - Hlavac, Jim; Saunders, Bernadette (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Interpreters and social workers frequently work together. They share some common goals and there is some similarity between the ethical guidelines that both professions follow. Despite this, interpreter-mediated social work encounters are rarely described, especially from the perspective of interpreting studies. Even more infrequent are studies that focus on trainee interpreters’ and social workers’ engagement in interprofessional education (IPE). Details of the design and delivery of IPE training sessions for interpreting and social work students, at Monash University from May 2017 to May 2019, are provided. The sessions featured two role-plays that simulated typical interactions in which interpreters and social workers work together. To assess the effectiveness of the IPE training in meeting both general and specific learning outcomes, three research questions were posed and the responses are reported in this article. The questions relate to the reported usefulness of role-plays in enabling the acquisition of desirable skills and knowledge; an increase in the level of knowledge of the other professional group, one’s own group and the perceived benefits for service-users; and the usefulness of pre- and post-interactional activities, such as briefing and debriefing. Responses to questionnaires were received from 218 of the 442 participating students. On a Likert scale with five gradings the average levels of agreement regarding the usefulness of role-plays are high, as are the levels of agreement about increases in knowledge of the other professional group and those of the students’ own professional group. The student informants reported that the skills they gained are likely to be beneficial to clients and patients with limited English proficiency. The trainees’ responses to their pre- and post-interactional interactions show that both groups registered a high level of agreement that briefings and debriefings are useful.